Electrical and dielectric properties of water - de Sousa, Francisco Ferreira; da Silva, Lilian Deyse Pinto; Freitas, Kellen Heloizy Garcia (Scientia Plena, 2017)
Water is one of the most important substances on planet. It’s constituted by hydrogen and oxygen elements, both of great importance chemistry and fundamental to human life. Although there are many studies about your physical and chemical properties in the scientific literature, much can be studied yet about this substance. In this study we report the electrical and dielectric properties of the water in liquid phase, such as impedance, dielectric permittivity and dipole moment as a function of frequency (1-20 kHz) in the temperature range between 288 and 314 K. The impedance and dielectric permittivity measurements were carried out in experimental apparatus equipped with an impedance analyzer. In addition, a capacitive system of parallel plate was and entire experiment was shielded to minimize electromagnetic interference effects (noise), and connected to the grounding of the laboratory electrical network. The dipole moment values were estimated applying the Kirkwood’s theory based on the definition of Onsager’s local field for polar liquids.